2006
DOI: 10.1007/s00384-006-0093-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct molecular patterns based on proximal and distal sporadic colorectal cancer: arguments for different mechanisms in the tumorigenesis

Abstract: These different features may reflect different genetic pathways of carcinogenesis and support the hypothesis of a different mechanism of cancer development between the proximal and the distal colon, with potential implications in the therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 72 publications
7
69
2
3
Order By: Relevance
“…Furthermore, mucinous tumors were found more frequently in the right side only when it was compared to rectum (p=0.014) ( Table V). This finding is also in agreement with some (5,12,16,17) but not all previous reports (19,20). Survival was not affected by tumor location in our hands (Table II) contrary to studies reporting a better survival for proximal colon cancers (8,12) and a worse survival for rectal tumors (21).…”
Section: ------------------------------------------------------------supporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, mucinous tumors were found more frequently in the right side only when it was compared to rectum (p=0.014) ( Table V). This finding is also in agreement with some (5,12,16,17) but not all previous reports (19,20). Survival was not affected by tumor location in our hands (Table II) contrary to studies reporting a better survival for proximal colon cancers (8,12) and a worse survival for rectal tumors (21).…”
Section: ------------------------------------------------------------supporting
confidence: 93%
“…We found that proximal cancers exhibit significantly higher tumor grade as compared to distal colon (p=0.009) and rectal cancers (p=0.003) ( Table V). This is in agreement with two previous reports (12,16), whereas other studies did not show any regional difference in tumor grade (17). Furthermore, mucinous tumors were found more frequently in the right side only when it was compared to rectum (p=0.014) ( Table V).…”
Section: ------------------------------------------------------------supporting
confidence: 93%
“…Previous reports have shown differences between the right-side colon (including the caecum, ascending colon, and transverse colon) and the left-side colon (including the descending colon, sigmoid colon, and rectum) in epidemiologic incidence (Gonzalez et al, 2001), morphology (Okamoto et al, 2005), and molecular alterations (Iacopetta, 2002;Azzoni et al, 2007). Meanwhile, other reports revealed these differences between the colon and rectum (Frattini et al, 2004;Kim et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…However, etiological pathways underlying colon cancers proximal to the splenic flexure are different from those distal to the splenic flexure and evidence that risk factors for tumors originating from different colorectal subsites vary is accumulating. 14,15 The aim of this study was to assess the association of prediagnostic plasma concentrations and dietary intakes of carotenoids and vitamins A, C and E with the risk of colon and rectal cancer in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) study. In addition, analyses for colon cancer were stratified by subsite.…”
mentioning
confidence: 99%